Investigation of the mechanical and tribological properties of scrap Al alloy MMCs reinforced with pumice/B4C particles through the electrodeposition of Ni-P surface coating - R. Jeevanantham; Dega Nagaraju (Results in Engineering)
In this research work, the scrap aluminium metal matrix composites were successfully fabricated through stir casting technique with novel combinations of reinforcements like pumice and B4C. The five different variants of composites are prepared, i.e., scrap and parent aluminium alloy without adding reinforcements; scrap aluminium alloy reinforced with pumice particles at the ratio of 2 wt. % and 1.5 wt. %; and scrap aluminium alloy reinforced with 1 wt. % of pumice and 1 wt. % of B4C. The mechanical and tribological properties of these composites were examined. The SEM and XRD analyses revealed the grain morphology of the composites. The scrap aluminium alloy reinforced with 2 wt. % pumice demonstrated the superior mechanical properties among the variants, with a 122.75 % enhancement in tensile strength and a 40.74 % increase in hardness relative to the other samples. The surface of the AMMCs was coated with Ni-P via electrodeposition to enhance corrosion and wear resistance. The Ni-P-coated AMMCs demonstrated wear and corrosion rates of 0.004 g and 0.19924 mm/a, respectively. FESEM pictures verified a consistent Ni-P coating with a thickness of 16 µm. The three-point bending test indicated coating delamination at a load of 722.2 N and a deflection of 9.09 mm. The elemental makeup of the AMMCs was verified using EDX analysis.